2021
DOI: 10.11113/amst.v25n3.224
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Stainless-Steel Membrane using a Closed-Batch iCVD Reactor for Oil/Water Separation

Abstract: Oil-spill is one of the major global issues facing society in this century. The aim of this study was to develop a steel-based membrane for selective separation of oil from oil/water mixture. For this purpose, a single-step, rapid and environmentally friendly closed-batch initiated chemical vapor deposition (iCVD) method was employed to deposit hydrophobic thin film on a stainless-steel mesh. Perfluorodecyl acrylate (PFDA) and tert-butyl peroxide (TBPO) were used as monomer and initiator, respectively. Owing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In the PPFDA spectrum, the intense peak at 1145 cm –1 is caused by the –CF 2 –CF 3 end group. The other sharp peaks observed at 1080 and 1199 cm –1 are caused by the asymmetric stretching and symmetric stretching of the –CF 2 –, respectively. The monomer spectrum contains peaks originating from the CC double bond at 1641, 1460, 1415, 1080, and 985 cm –1 , which are absent in the polymer spectrum indicating that the polymerization pathway during iCVD is through the double bond of the vinyl monomer . Hence, it can be concluded that iCVD is able to produce PPFDA films on GO with high retention of the pendant perfluoroalkyl group of the monomer.…”
Section: Resultsmentioning
confidence: 96%
“…In the PPFDA spectrum, the intense peak at 1145 cm –1 is caused by the –CF 2 –CF 3 end group. The other sharp peaks observed at 1080 and 1199 cm –1 are caused by the asymmetric stretching and symmetric stretching of the –CF 2 –, respectively. The monomer spectrum contains peaks originating from the CC double bond at 1641, 1460, 1415, 1080, and 985 cm –1 , which are absent in the polymer spectrum indicating that the polymerization pathway during iCVD is through the double bond of the vinyl monomer . Hence, it can be concluded that iCVD is able to produce PPFDA films on GO with high retention of the pendant perfluoroalkyl group of the monomer.…”
Section: Resultsmentioning
confidence: 96%